Through the Looking Glass: An Empirical Look at Discrimination in the Federal Income Tax Rate Structure. - Jensen, Herbert L.; Wyndelts, Robert W. (The Accounting Review, 1976)
This article focuses on various concepts of equity and cites a study of the discrimination in the federal income tax rate structure. Given these three conflicting views of equity in the federal income tax rate structure, the taxable incomes of the spouses were allowed to vary from $1,000 to $40,000 in $1,000 steps. Then the tax burdens for all such combinations under the 1975 tax rate schedules for single and married taxpayers were computed. Only the impact of the federal income tax rate structure was considered in this study. The primary causes of distortions between singles and married that have been ignored were the maximum standard deduction, the low income allowance, exemptions for children, and child care deductions. It was noticed that when equity was defined as having economic units with equal incomes be taxed equally, a burden on single taxpayers emerged. The tax burdens for the lower income levels have been entered on the appropriate intersection to provide some guideline for the locus of the zero tax burden curve in the obtained graph. It is concluded that the tax rate structure has very different implications for taxpayers depending on their taxable incomes.